Changing the electronic request form proves to be an effective tool for optimizing laboratory test utilization in the emergency department. (June 2017) - Lapić, Ivana; Juroš, Gordana Fressl; Rako, Ivana; Rogić, Dunja
Highlights: Appropriate laboratory utilization more often needs to be initiated by the laboratory. Omission of laboratory tests from the electronic request form resulted in a reduced use of tests. Notable savings have been achieved by reducing exclusively the tests classified as low-cost. Simple interventions can give satisfactory results if planned carefully. Abstract: Objectives: Appropriate laboratory utilization more often than not needs to be initiated by the laboratory. This study was performed to analyze the impact on test ordering patterns in the emergency department obtained by omitting certain tests from the electronic tick box request form. The tests could still be ordered by writing the full name of the test or by a phone call. Methods: Erythrocyte sedimentation rate (ESR), fibrinogen, aspartate aminotransferase (AST), calcium and lipase were omitted from the electronic request form and could subsequently be ordered either by phone or a typed-in request. A reflex testing protocol was elaborated for reduction of creatine kinase (CK) and CK-MB analyses. All interventions were introduced with prior consultation with clinical staff and according to current guidelines. The reduction of test orders and costs in the post-intervention period was assessed. All data were retrieved retrospectively from the laboratory information system (LIS). Results: Disappearance from the tick box request form resulted in a significant decrease in the number of requests for targeted tests in the post-intervention year, mostly affecting AST and fibrinogen (83% and 79% reduction of ordering, respectively), followed by a 58% reduction in calcium orders, and 54% and 43% reductions in ESR and lipase requests, respectively. A substantial reduction in CK requests was also observed, while CK-MB requests almost disappeared. Annual cost savings that emerged from all implemented interventions were estimated to be 19, 445€. Conclusion: Significant reduction in ordering of selected tests was achieved simply by limiting their availability in hospital computerized order entry (COE) system. The present data suggest that removal of laboratory tests from the electronic request form can be an effective tool for changing physicians' test ordering behavior.